A high‐performance biomarker panel for Alzheimer's disease screening and staging identified by large‐scale plasma proteomic profiling. (31st December 2021) - Jiang, Yuanbing; Zhou, Xiaopu; Ip, Fanny C.F.; Chan, Philip; Chen, Yu; Lai, Nicole Chit Hang; Cheung, Kit; Lo, Ronnie M.N.; Tong, Estella Pui‐Sze; Wong, Bonnie W.Y.; Chan, Andrew L.T.; Mok, Vincent C.T.; et al.
Abstract: Background: Blood proteins are emerging candidate biomarkers for Alzheimer's disease (AD). A comprehensive investigation of the AD blood proteome will help identify additional biomarkers to delineate the disease's pathways and define specific AD stages. Method: We quantified 1, 160 plasma proteins in a Hong Kong Chinese cohort (n = 106 AD patients, n = 74 healthy controls) by high‐throughput proximity extension assay to identify AD‐associated plasma proteins. Result: Plasma proteins involved in diverse biological processes were found to be dysregulated in AD. A subset of plasma proteins was selected to represent the AD plasma protein profile, which formed the basis of a scoring system that can accurately classify AD and associated endophenotypes. In addition, we showed that certain plasma proteins and biological processes exhibit stage‐specific dysregulation in AD, thus adding biological annotations to AD stages. Conclusion: This study comprehensively profiled the AD plasma proteome and serves as a foundation for a high‐performance, blood‐based test for clinical AD screening and staging.